Calculation of the Hydrodynamic Resistance of Appendages on Conventional Vessels - Polyzos, Stylianos (Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2017)
The present thesis deals with the numerical formulation, programming and validation of a method for solving the viscous flow problem around the appendages on conventional vessels. The proposed method is based on the overlapping blocks approach, part of the Finite Volume family of methods. The proposed method is based upon and expands the LSMH method for solving the resistance and propulsion “bare” hull problem at model and full scale. The LSMH method solves the Reynold’s Averaged Navier-Stokes (RANS) in conjunction with the two equations k-ε or k-ω-SST turbulence models. Introduced in this thesis is the use of Total Variation Diminishing differencing scheme with Minmod limiter function. The use of this higher-order scheme aims at increasing the accuracy of the method. The coupled momentum and mass continuity equations are solved in a staggered grid arrangement, by means of the SIMPLE algorithm. The propeller action is modeled via the classical actuator disk method, taking into account both axial and tangential body forces. The flow around the hull is modeled using structured body fitted grids, comprising orthogonal curvilinear 2-D O-type grids, generated by means of the conformal mapping technique. The method is now expanded so that up to three grid blocks may be employed, namely a C-O-type around the bow, an H-O-type around the mid and stern of the ship and finally an H-H-type abaft the transom stern of ships. Using the new arrangement, the method can more accurately predict the resistance of ships with “full” lines near the bow and also predict the effect of a “wetted” transom stern. In the original LSMH software, the free surface is calculated either via a surface tracking RANS based method or via a surface tracking potential flow method. A novel hybrid method is proposed in this thesis. In this new method, the free surface calculated by means of the potential solver is corrected via a surface tracking RANS method. The correction is applied only at the aft half and the wake of the ship while boundary conditions on the free surface are specially treated, in order to avoid convergence problems. The proposed method is validated by comparing the calculated free surface for two ship designs with experimental data. A new method for solving the flow problem around the appendages is then proposed. The method is based on the Overlapping Grid Block approach, where the flow around each component of the ship appendages is solved using a separate grid block. The blocks overlap and information is passed-on from one block to the other through the boundary conditions of the later. A method for the parametric representation of ship appendages is presented in this thesis. Then, the method for generating the individual grid blocks is presented in detail along with the proposed method for the exchange of flow variables between blocks. The LSMH RANS solver is modified to handle the new blocks and the exchange of flow variables according to the overlapping block approach. The ability of the method to solve the flow past individual blocks is then demonstrated through a number of numerical tests for each of the individual blocks. The new software, the result of the research carried out in this thesis, is used to solve the resistance and propulsion problem for the “Dyne” tanker. Calculations are performed at both model and full scale and for both the “bare” hull and the case of the ship with the rudder. The model scale calculations include symmetric and asymmetric flow calculations, as well as calculations with wall functions and near wall treatment instead. The rudder of the “Dyne” tanker is modeled using a separate grid block. A grid independence test is performed, in order to determine the required grid size for the rudder block. Also a series of tests is presented, to evaluate the effectiveness of the overlapping block setup. Finally resistance and propulsion calculations are performed for the ship with the rudder, at model and full scale. All numerical results are compared with the available experimental data.